Interaction between infection, nutrition and immunity in tropical medicine - Pereira,P. C. M. (2003)
Host nutritional state has an important role in susceptibility to bacteria, parasites, and viral infections. Infection precipitates the appearance of signs and symptoms of nutrition deficiencies in the undernourished; this can aggravate infection evolution. Infection stimulates specific and non-specific host defense mechanisms; these are directly influenced by the nutritional state of micro- and macronutrients. Immune alterations, which are closely related to nutritional status, markedly contribute to a higher susceptibility to infectious agents and can also contribute to worsening nutritional state, forming a vicious cycle.